INNOVATIVE TECHNOLOGIES AS A TOOL FOR DEVELOPING STUDENTS’ COMPOSITIONAL THINKING IN ART EDUCATION - Jalolov Shavkat Choriyevich (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
Abstract: This article discusses the impact of innovative technologies on enhancing students’ compositional thinking in art education. Emphasis is placed on the use of digital tools, interactive learning platforms, flipped classrooms, and project-based learning as methods to improve artistic competencies, creative problem-solving, and analytical reasoning. The study highlights pedagogical strategies and technological integrations that support independent and critical thinking among students.